Potential of bank filtration in tropical environments : biogeochemical analysis of tropical hyporheic zone and simulation of algae passage in porous media - FREITAS, Jonathas Barbosa de Araújo (2023)
Bank Filtration (BF) is an efficient and cost-effective technology for water treatment. During the BF process, there is interaction between a surface water source and its underlying aquifer. Therefore, understanding the processes occurring in the hyporheic zone is crucial for the application of this technology. Biogeochemical markers, such as environmental isotopes, elemental markers and hyporheic meiofauna are important for studying this zone, especially in tropical regions where little research has been conducted on this topic. Furthermore, a global challenge is the eutrophication of water sources, leading to algal blooms and impairing water treatment through conventional methods. In this context, this thesis analyzed the physicochemical and biological characteristics of the hyporheic zone in the Beberibe River (Northeast of Brazil) through sedimentological analysis (grain size and organic matter and calcium carbonate contents), isotopic markers (δ15N and δ13C), elemental markers (total organic carbon, total nitrogen, and C/N ratio), and biological marker (meiofauna). It also investigated the influence of different temperatures (10°C, 20°C, and 30°C) on algal retention through laboratory column tests with different flow rates. These experiments were conducted using laboratory-cultivated samples (Microcystis Aeruginosa) and enriched samples from the Elbe River (Germany). The results revealed that domestic wastewater discharge had the greatest impact on the characteristics of the hyporheic zone, including higher meiofauna abundance, fine sediments, organic matter and calcium carbonate. These factors contribute to the formation of a colmation layer that aids in the retention and biodegradation of pollutants. In the algal column tests, temperature and flow rate showed a significant impact on retention, with lower flow rates and temperatures between 20°C and 30°C favoring algal retention and biodegradation. In conclusion, it was found that the combination of eutrophication and tropical conditions creates favorable conditions for the formation of a colmation layer and the attenuation of pollutants during the BF process. These results are relevant for the application of BF in tropical regions, particularly in developing countries in Latin America, Africa and South Asia.